2019
DOI: 10.1002/jemt.23377
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the properties of gamma irradiated of polytetrafluoroethylene fibers

Abstract: The physical, thermal, and chemical properties of gamma-irradiated polytetrafluoroethylene (PTFE) fibers were investigated using X-ray diffraction (XRD), differential scanning calorimetry (DSC), and Fourier transform infrared (FTIR) spectroscopy. Scanning electron microscopy (SEM) was also used to analyze the surface morphology of irradiated fiber samples. PTFE fiber samples were irradiated by gamma radiation doses ranging from 3 kGy to 40 kGy. The XRD analyses and DSC measurements showed the improvement of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The increase in crystallinity upon irradiation can be explained by increased cross-linking at certain irradiation doses. The possible radiation rupture of the macromolecular chain, which causes the mobility of the resulting molecular fragments of the polymer, leads to the removal of residual stress in the amorphous region and a decrease in the likelihood of the entanglement of macromolecular chains with the formation of additional small crystallites [27]. Higher crystallinity (81%) is characteristic of the sample with a lower molecular weight (TOMFLON TM ), which is consistent with the results of TG and DSC (Figure 5).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The increase in crystallinity upon irradiation can be explained by increased cross-linking at certain irradiation doses. The possible radiation rupture of the macromolecular chain, which causes the mobility of the resulting molecular fragments of the polymer, leads to the removal of residual stress in the amorphous region and a decrease in the likelihood of the entanglement of macromolecular chains with the formation of additional small crystallites [27]. Higher crystallinity (81%) is characteristic of the sample with a lower molecular weight (TOMFLON TM ), which is consistent with the results of TG and DSC (Figure 5).…”
Section: Resultssupporting
confidence: 85%
“…Methods for the surface modification of PTFE powder to improve compatibility with hydrocarbon elastomers and reduce agglomeration have also been reported [22,[24][25][26]. It is known that high-energy gamma radiation and electron beam radiation affect the physical and mechanical properties of PTFE [27][28][29][30]. For instance, radiation-treated PTFE exhibits a better reinforcing effect than non-irradiated PTFE in polar systems [23].…”
Section: Introductionmentioning
confidence: 99%
“…Δ H m , which reflected the crystalline fraction in polymers, could be raised rapidly from 22.79 J/g for pristine PTFE to more than 63.64 J/g for irradiated PTFE. The increase of Δ H m revealed that the chain scission produced lots of small molecular fragments to reduce the number of entanglements per molecule, then enhanced the chain mobility and improved the degree of crystallinity of PTFE 34,46,47 …”
Section: Resultsmentioning
confidence: 99%